Agency theory, stewardship theory and stakeholder theory: an Islamic perspective - Htay, Sheila Nu Nu; Syed, Ahmed Salman (IJMRA, 2013)
Recent events have placed an emphasis on the need for effective corporate governance. Corporate scandals leading to the downfall of financial giants such as Enron and WorldCom in 2003 and the global financial crisis of 2008-2009 have revealed serious inadequacies in the quality of corporate governance at an international level. Existing standards are lack in providing the necessary guidelines for checks and balances that corporations need to cultivate sound business practices. There are various conventional theories, namely the agency theory, stewardship theory and stakeholder theory articulated throughout time in determining the most effective system of corporate governance. Many developed and developing countries as well as organizations have laid down the Best Practices for Corporate Governance based on the prevailing corporate governance theories. To the extent of the researchers’ knowledge, corporate governance problems become more serious day by day even at the existence of the tight rules and regulation of corporate governance. Therefore, these governance problems motivate the researchers to examine the foundation of the corporate governance guidelines, i.e. corporate governance theories from the unconventional and non-mainstream aspect. The objective of this paper is to examine agency theory, stewardship theory and stakeholder theory from an Islamic Perspective.